Profile and sociocultural analysis of humanities teachers of the Military School of Santa Maria – RS (Research, Society and Development, 2019)
The humanities teaching at the Military School of Santa Maria is taught by teachers of different profiles, who have different characteristics and perceptions regarding their professional performance and teaching practices. From a practical point of view, the sociocultural characteristics of these different profiles in the educational space reflect in the teaching and, in this sense, it becomes important to analyze and reflect on the subject and to contribute with analyzes that aid the school management. In this article, the main objective is to obtain and analyze data that allow to describe the different characteristics of the diverse professorial profiles existing in the Military School of Santa Maria-RS and, in this way, to bring contributions to the management and for the teachers improve the humanities teaching. The methodology consisted of qualitative and quantitative documentary analysis and the application of a questionnaire to humanities teachers. It was possible to observe the importance of pedagogical, functional and pedagogical data knowledge concerning the trajectories of the teachers and, finally, to present considerations that reflect the school environment in aspects such as pedagogical knowledge, teaching experience, function performed at school, professional objectives such as form of a theoretical quantitative support for decision-making in the humanities area.